Penegakkan Hukum Terhadap Tindak Pidana Perundungan dalam Dunia Maya (Cyberbullying) di Kota Kupang - Michele Gisela Dubu; Rudepel Petrus Leo; Orpa Ganefo Manuain (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The world has entered the era of modernization and affects increasingly sophisticated technology and information, but this has resulted in many individuals who abuse the internet as a means of committing crimes, one of which often occurs is cyberbullying or (cyberbullying). The crime of cyberbullying has been regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning the ITE Law and the Criminal Code (KUHP) which is elaborated to become the basis for authorized law enforcement in enforcement efforts. This research is an empirical juridic research. The location of the research in the East Nusa Tenggara regional police area, the data collection method is by interviews, documentation studies and observations. The collected data is then analyzed and then presented in a qualitative descriptive manner. The results of the research on law enforcement through 2 stages, among others, preventive efforts and repressive efforts, then inhibiting factors in law enforcement, among others, limited budget and tools for investigation and investigation so that it is difficult to find evidence if the perpetrator uses a fake account without personal data or phone number, besides that Article 74 of the Criminal Code has regulated the expiration of the complaint offense so that the victim must immediately report the crime he has experienced. As for the suggestion, it is hoped that the consistent active role of law enforcers to socialize rules and ethics in the use of social media and maximize law enforcement efforts for perpetrators of criminal acts to the court stage. The government can make a special formula related to the expiration of complaints for cyberbullying cases in the ITE Law. It is hoped that the public will have a high legal awareness in the use of social media so as to prevent criminal acts committed through cyberspace.